Strategi Pengembangan Usaha Ternak Sapi Potong di Desa Tulabolo Barat Kecamatan Suwawa Timur - Asimin, Putri Utami; Baruwadi, Mahludin; Aisyah R, St. (Jurnal MeA (Media Agribisnis), 2024)
Beef cattle are a type of animal that is bred continuously. Increasing the capacity of beef cattle needs to be done to meet the community's increasing demand for meat. This study seeks to analyze strategies for developing beef cattle farming businesses as a viable option for farmers looking for alternative employment prospects outside the mining sector. This research uses primary and secondary data collection methods which include observation, interviews and documentation. Data processing and analysis involves the use of several methods: (1) EFE (external factor evaluation) and IFE (internal factor evaluation) matrix analysis; (2) internal external (IE) matrix which graphically represents the combined score of the IFE and EFE matrices; (3) SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to identify various factors systematically. The research results show that the internal factor variable has a value of 3.07, but the external factor variable has a value of 3.00. The results of this research indicate that the beef cattle farming business in West Tulabolo Village is currently experiencing significant growth by effectively utilizing existing resources to increase the beef cattle population. This study shows that the use of SO (Strengths-Opportunities) techniques provides the greatest value in facilitating aggressive strategies for the growth and expansion of beef cattle farming businesses.Â Â